Association of obesity with Helicobacter pylori infection: A retrospective study - Xu, Mei-Yan (World J Gastroenterol, 2017)
AIM: To explore the association between Helicobacter pylori (H. pylori) infection and obesity/weight gain in a Chinese population. METHODS: Our primary outcome was the change in body mass index (BMI). The generalized linear models were used to explore the association between H. pylori infection and the change of BMI, and the logistic regression models were used to explore the association between H. pylori infection and obesity. RESULTS: A total of 3039 subjects were recruited and analyzed, of which 12.8% were obese. The prevalence of H. pylori infection was 53.9% (1639/3039) overall and 54.6% (212/388) in the obese subjects. The change of BMI in the H. pylori (+) group was not significantly higher than that in the H. pylori (-) group after adjustment for potential confounding factors [RR = 0.988, 95%CI: 0.924-1.057, P = 0.729]. The prevalence of obesity decreased 1.1% in the H. pylori (+) group and 0.5% in the H. pylori (-) group. The RR of H. pylori infection for obesity was 0.831 (95%CI: 0.577-1.197, P = 0.321) after the adjustment. CONCLUSION: H. pylori infection was not associated with overweight/obesity observed from the retrospective study in this Chinese population.